1-(4,5,6,7-Tetrahydrothieno[3,2-c]pyridin-5-yl)-2-{4-[3-(trifluoromethyl)phenyl]piperazin-1-yl}ethanone - Zhi, Shuang (International Union of Crystallography, 2012)
In the title molecule, C(20)H(22)F(3)N(3)OS, the piperazine ring has a chair conformation, and the N—C(=O)—C—N torsion angle is −59.42 (14)°. In the crystal, weak C—H⋯O and C—H⋯π interactions link the molecules into layers parallel to (101).